The role of the accountants: New challenges ahead / Allan Chang - Chang, Allan (Institut Teknologi MARA Cawangan Sarawak, 1990)
A general manager of a large trading company once commented on his accountant: I "When I look at you, 1 see only Dollars and Cents in your eyes". Another unkind word once uttered by a manufacturer of fibre board furniture at a seminar runs like this: "The return on investments of these machines are reasonably good in the long run, but it is damned accountants who like to see only a smooth cash flow." However, the Chief Minister of Sarawak at a dinner organised by the Malaysian Institute of Accountants (MIA) in May 1988 has more kind words to say: "The accountants have a great role to play in nation building with its rapid industrialisation programme, but they should avoid producing too many figures which bore the business even though they would like to see other figures elsewhere."